2009
DOI: 10.1002/jnr.22087
|View full text |Cite
|
Sign up to set email alerts
|

Possible promotion of neuronal differentiation in fetal rat brain neural progenitor cells after sustained exposure to static magnetism

Abstract: We have previously shown significant potentiation of Ca(2+) influx mediated by N-methyl-D-aspartate receptors, along with decreased microtubules-associated protein-2 (MAP2) expression, in hippocampal neurons cultured under static magnetism without cell death. In this study, we investigated the effects of static magnetism on the functionality of neural progenitor cells endowed to proliferate for self-replication and differentiate into neuronal, astroglial, and oligodendroglial lineages. Neural progenitor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…The increase in Tuj1 expression resulted in a decrease in GFAP labeled cells but not in a decrease of non-neuronal cells. This is consistent with studies that have shown that proneural genes including Math1 bias neuronal differentiation at the expense of glial differentiation [32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…The increase in Tuj1 expression resulted in a decrease in GFAP labeled cells but not in a decrease of non-neuronal cells. This is consistent with studies that have shown that proneural genes including Math1 bias neuronal differentiation at the expense of glial differentiation [32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…Several in vitro studies [Hirai and Yoneda, ; Nakamichi et al, ] reported that sustained exposure to SMF could facilitate cellular functionality and differentiation in immature neurons and neural progenitor cells. However, this beneficial effect was obtained at the cost of a suppressed proliferation for self‐renewal, which absolutely is not advantageous for neural regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Applied electromagnetic fields (EMFs) inhibit proliferation and promote differentiation of mouse bone marrow mesenchymal stem cells (Wu et al 2005) and embryonic stem cells (Ventura et al 2005), and stimulate the maturation and differentiation of cerebellar granule neurons in newborn rat (Lisi et al 2005). Nakamichi and colleagues showed that exposure to a 100 mT static magnetic field (SMF) reduced proliferation of NPCs in the fetal rat brain (Nakamichi et al 2009). Thus, disturbance of the GMF could modulate proliferation and differentiation of NPCs/NSCs.…”
Section: Introductionmentioning
confidence: 99%